1999
DOI: 10.1103/physrevb.60.11855
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced asymmetry in the crystallization behavior during constant heating and cooling of a bulk metallic glass-forming liquid

Abstract: The crystallization behavior of the supercooled bulk metallic glass-forming Zr 41 Ti 14 Cu 12 Ni 10 Be 23 liquid was studied with different heating and cooling rates. A rate of about 1 K/s is sufficient to suppress crystallization of the melt upon cooling from the equilibrium liquid. Upon heating, in contrast, a rate of about 200 K/s is necessary to avoid crystallization. The difference between the critical heating and cooling rate is discussed with respect to diffusion-limited growth taking classical nucleati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
90
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 152 publications
(98 citation statements)
references
References 17 publications
6
90
1
1
Order By: Relevance
“…The values of 1/Q 1 3 upon reheating reproduce the values during cooling for each respective temperature range, except for the range from 770 to 1,091 K. In this temperature interval (770-1,091 K), the sample devitrified and measurements on the liquid state are not possible. The crystallization upon reheating beginning at 770 K is expected if the (re-)heating rate of the supercooled liquid is not so fast as to avoid the crystallization altogether (o200 K s À 1 ), according to the time-temperaturetransformation diagram of Schroers et al 31 . It should be pointed out that a discontinuity in 1/Q 1 3 upon reheating is not obvious in the temperature range, where the c p peak is observed around 1,100-1,200 K, from the limited data points collected, due to the narrow time window of the detection.…”
Section: Resultsmentioning
confidence: 99%
“…The values of 1/Q 1 3 upon reheating reproduce the values during cooling for each respective temperature range, except for the range from 770 to 1,091 K. In this temperature interval (770-1,091 K), the sample devitrified and measurements on the liquid state are not possible. The crystallization upon reheating beginning at 770 K is expected if the (re-)heating rate of the supercooled liquid is not so fast as to avoid the crystallization altogether (o200 K s À 1 ), according to the time-temperaturetransformation diagram of Schroers et al 31 . It should be pointed out that a discontinuity in 1/Q 1 3 upon reheating is not obvious in the temperature range, where the c p peak is observed around 1,100-1,200 K, from the limited data points collected, due to the narrow time window of the detection.…”
Section: Resultsmentioning
confidence: 99%
“…The DSC used is limited to a maximum heating rate of 3.33 K/s, and it has been shown that a heating rate of approximately 200 K/s is necessary to avoid crystallization upon heating. 16 Following the isothermal anneals, constant heating rate measurements were performed on the samples in order to determine whether they were completely crystalline. Surprisingly, all the alloys showed some remaining amorphous fraction after isothermal annealing, regardless of annealing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] It is found that the crystallization process is sensitive to alloy composition, 4 applied pressure, [5][6][7][8][9][10] annealing temperature, 11,12 and heating rate 13 so on. Schroers et al 13 has proved that a rate of about 200 K/s upon heating can avoid any crystallization events in the Zr 41 Ti 14 Cu 12.5 Ni 10 Be 22.5 bulk metallic glass.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] It is found that the crystallization process is sensitive to alloy composition, 4 applied pressure, [5][6][7][8][9][10] annealing temperature, 11,12 and heating rate 13 so on. Schroers et al 13 has proved that a rate of about 200 K/s upon heating can avoid any crystallization events in the Zr 41 Ti 14 Cu 12.5 Ni 10 Be 22.5 bulk metallic glass. Previous work [5][6][7][8][9][10]14,15 has proved that applied pressure has a noticeable effect on crystallization, and is a powerful tool for modifying and controlling microstructure of metallic glasses.…”
Section: Introductionmentioning
confidence: 99%